Autobiographical memory: A candidate latent vulnerability mechanism for psychiatric disorder following childhood maltreatment. (October 2017) - McCrory, Eamon J.; Puetz, Vanessa B.; Maguire, Eleanor A.; Mechelli, Andrea; Palmer, Amy; Gerin, Mattia I.; Kelly, Philip A.; Koutoufa, Iakovina; Viding, Essi
Abstract : Background: Altered autobiographical memory (ABM) functioning has been implicated in the pathogenesis of depression and posttraumatic stress disorder and may represent one mechanism by which childhood maltreatment elevates psychiatric risk. Aims: To investigate the impact of childhood maltreatment on ABM functioning. Method: Thirty-four children with documented maltreatment and 33 matched controls recalled specific ABMs in response to emotionally valenced cue words during functional magnetic resonance imaging. Results: Children with maltreatment experience showed reduced hippocampal and increased middle temporal and parahippocampal activation during positive ABM recall compared with peers. During negative ABM recall they exhibited increased amygdala activation, and greater amygdala connectivity with the salience network. Conclusions: Childhood maltreatment is associated with altered ABM functioning, specifically reduced activation in areas encoding specification of positive memories, and greater activation of the salience network for negative memories. This pattern may confer latent vulnerability to future depression and posttraumatic stress disorder.